2017
DOI: 10.9745/ghsp-d-17-00203
|View full text |Cite
|
Sign up to set email alerts
|

Food Security and Nutrition Outcomes of Farmer Field Schools in Eastern Democratic Republic of the Congo

Abstract: A farmer field school program in food-insecure areas had positive impacts on household food security but not child nutritional status. Similar agricultural interventions may benefit food security, but the more difficult-to-achieve improvements in child nutrition status may require more focused and integrated programming approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…These reductions were associated with a reduction in pesticide applications, the selection of less toxic products or the use of improved methods of personal protection (Chhay 2017;Cole et al 2007;Morales-Abubakar et al 2013;FAO 2016b;Mancini et al 2009;Jørs et al 2014), but some studies found no effect of the FFS on pesticide applications (see 3.3). There was also a positive effect of the FFS on the diversity of food and nutrition at household level (DANIDA 2011;Weinhardt et al 2016;Doocy et al 2017;Kuria 2014).…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…These reductions were associated with a reduction in pesticide applications, the selection of less toxic products or the use of improved methods of personal protection (Chhay 2017;Cole et al 2007;Morales-Abubakar et al 2013;FAO 2016b;Mancini et al 2009;Jørs et al 2014), but some studies found no effect of the FFS on pesticide applications (see 3.3). There was also a positive effect of the FFS on the diversity of food and nutrition at household level (DANIDA 2011;Weinhardt et al 2016;Doocy et al 2017;Kuria 2014).…”
Section: Quality Of Lifementioning
confidence: 99%
“…In a study in the DR Congo, the FFS intervention took two years, and after completion, many farmers formed farmer business associations to improve access to credit and marketing (Doocy et al 2018;Doocy et al 2017). The study followed FFS households every six months for 3.5 years.…”
Section: Access To Services and Marketsmentioning
confidence: 99%
“…One of most extensive top-down programmes for SAD that has evolved during that past 30 years is the Farmer Field School (FFS) programme initiated by the Food and Agricultural Organization (FAO) (FAO, 2017;Rocha, 2017;Settle, Soumare, Sarr, Garba, & Poisot, 2014). The FFS programme focuses explicitly on increasing farmers' knowledge of environmentally friendly farming to increase agricultural productivity and farmers' income (Chhay et al, 2017;Doocy et al, 2017;Hussain, Rehman, Bibi, Khalid, & Khalid, 2017;Rocha, 2017;Settle et al, 2014). Recent studies (Doocy et al, 2017;Rocha, 2017;Scheba, 2017), however, show that this programme has not always been as successful as envisioned (in some cases with no effect at all on the farming techniques deployed or on productivity).…”
Section: Introductionmentioning
confidence: 99%
“…The FFS programme focuses explicitly on increasing farmers' knowledge of environmentally friendly farming to increase agricultural productivity and farmers' income (Chhay et al, 2017;Doocy et al, 2017;Hussain, Rehman, Bibi, Khalid, & Khalid, 2017;Rocha, 2017;Settle et al, 2014). Recent studies (Doocy et al, 2017;Rocha, 2017;Scheba, 2017), however, show that this programme has not always been as successful as envisioned (in some cases with no effect at all on the farming techniques deployed or on productivity). Lack of awareness of the need for change for SAD, and lack of coordination between actors, are the two main causes named, in addition to lack of market, financial and other supporting infrastructures (Doocy et al, 2017;Scheba, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation